Nutritional Status, Physical Activity, Sedentary Behavior, Diet, and Lifestyle in Childhood: An Analysis of Respiratory Diseases in Adolescence - De Moraes-Ferrari, G (Sao Paulo Pediatric Society, 2021)
Objective: To evaluate the association between nutritional status, physical activity, sedentary behavior, diet, and lifestyle in childhood with respiratory diseases during adolescence. Methods: Prospective study conducted in Saõ Caetano do Sul, Saõ Paulo-Brazil, as part of the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE). During childhood, indicators of lifestyle (body composition, physical activity, sedentary behavior, diet) and family environment were measured in 2012 and 2013. After five years, participants answered the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire for the diagnosis of respiratory diseases (asthma and/or rhinitis). Analyses were determined by logistic regression. Results: A total of 168 schoolchildren (56% boys) were evaluated, and the prevalence of asthma and rhinitis accounted for 15.5 and 25.6%, respectively. Whole milk consumption (Odds Ratio [OR]=1.24; 95% confidence interval [95%CI] 1.03-1.49), having a television in the bedroom (OR=0.29; 95%CI 0.12-0.71), and attending physical education classes ≥2 times/week (OR=0.30; 95%CI 0.11-0.81) in childhood were associated with the presenceof asthma in adolescence. Factors significantly associated with rhinitis were as follows: Female participants (OR=2.45; 95%CI 1.20-4.98) and whole milk consumption (OR=1.21; 95%CI 1.04-1.40). Conclusions: Higher consumption of whole milk, not having a television in the bedroom, few physical education classes, and being a girl were factors associated with respiratory diseases. Public policies should be directed toward a healthier lifestyle and the prevention of respiratory diseases. © 2021 Sao Paulo Pediatric Society. All rights reserved.